SPATIAL AUTOCORRELATION ANALYSIS OF PULMONARY TUBERCULOSIS CASES IN CENTRAL JAVA PROVINCE - Puspita Septiani (Universitas Airlangga, 2024)
Tuberculosis is a disease that is easily transmitted and causes worry across the world. Central Java Province became one of the regions contributing the most tuberculosis cases in Indonesia in 2022, which amounted to 22,249 cases. This study aims to examine the local and global spatial autocorrelation of pulmonary tuberculosis cases in the Central Java Province in 2022. This research is an analytic observational research with an ecological study design. The unit of analysis used was 35 districts/cities. This study used secondary data from the Health Profile of Central Java Province in 2022. Data analysis used Moran's Index and Local Indicators of Spatial Associaton (LISA) methods with queen contiguity weighting in Geoda software. The results showed that Moran's index value of the global autocorrelation test on the number of pulmonary tuberculosis cases was 0.505. The results of the bivariate LISA test obtained the p value of tuberculosis cases with population, population density, and number of health facilities of 0.002, 0.449, and 0.007, respectively, with the Moran index value of 0.3111, 0.0075, and 0.2384 respectively. There are 9 spatially significant areas between population, population density, and number of health facilities with tuberculosis cases. This study concludes that there is a positive spatial autocorrelation (clustering pattern) of pulmonary tuberculosis cases in Central Java Province in 2022. In addition, there is positive spatial autocorrelation between population and number of health facilities with TB cases (clustering pattern) and there is no spatial autocorrelation between population density and TB cases.